2021
DOI: 10.1002/kin.21475
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of OH and OD radicals with simple thiols and sulfides studied by infrared chemiluminescence of isotopic water products: Reaction OH + CH3SH revisited

Abstract: Vibrational excitation of the H2O, HOD, and D2O product molecules from the reactions of OH and OD radicals with CH3SH, CH3C(O)SH, (CH3)3CSH, H2S, and CH3SCH3 was determined by modeling the infrared emission spectra using a renovated and extended set of model spectroscopic bands. Using the deuterated reactant, CH3SD, it was possible to separate spectra of abstraction from C‐ and S‐sites, which allowed measurement of branching fractions and kinetic isotope effects for individual channels. For the OH + CH3SH reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
1
8
1
Order By: Relevance
“…The OH radical reacts with CH 3 SH by H-abstraction from either the thiol group forming the CH 3 S radical or the methyl group forming the CH 2 SH radical. The CH 3 S yield was reported to be 1.1 ± 0.2 by direct kinetics measurement and 0.87 ± 0.03 based on the H 2 O and HOD yields from experiments with deuterated species . In a recent theoretical ab initio/RRKM study, the CH 3 S yield was found to be 0.98 at 298 K and 760 Torr .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The OH radical reacts with CH 3 SH by H-abstraction from either the thiol group forming the CH 3 S radical or the methyl group forming the CH 2 SH radical. The CH 3 S yield was reported to be 1.1 ± 0.2 by direct kinetics measurement and 0.87 ± 0.03 based on the H 2 O and HOD yields from experiments with deuterated species . In a recent theoretical ab initio/RRKM study, the CH 3 S yield was found to be 0.98 at 298 K and 760 Torr .…”
Section: Resultsmentioning
confidence: 95%
“…The CH 3 S yield was reported to be 1.1 ± 0.2 by direct kinetics measurement 53 and 0.87 ± 0.03 based on the H 2 O and HOD yields from experiments with deuterated species. 54 In a recent theoretical ab initio/RRKM study, the CH 3 S yield was found to be 0.98 at 298 K and 760 Torr. 55 Here, we assume a unity yield of CH 3 S from the OH + CH 3 SH reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other studies have shown that the reaction of MeSH with OH occurs primarily at the S-H group (0.87 ± 0.03) forming CH3S•, with a minor channel of H-abstraction from the methyl group (0.13 ± 0.03) (Butkovskaya and Setser, 2021). Recent ab initio/RKKM calculations determined the CH3S• yield from MeSH + OH at 298 K and 760 torr to be 0.98 (Mai et al, 2020).…”
Section: Atmospheric Fate Of Meshmentioning
confidence: 99%
“…While the bimolecular rate constants of MeSH with the primary atmospheric oxidants (OH, BrO, NO 3 , Cl) are known, there has been limited study on the reactive intermediates or yields of stable products from MeSH oxidation (Butkovskaya and Setser, 1999;Tyndall and Ravishankara, 1991). However, oxidation of MeSH by OH (Reaction R1) has been shown to produce the methyl thiyl radical (CH 3 S) at a yield of 1.1 ± 0.2 (Tyndall and Ravishankara, 1989), providing a mechanistic link to known reactions in the DMS H abstraction pathway (Reaction R1) (Barnes et al, 2006), as shown in the simplified reaction scheme in Fig.…”
Section: Atmospheric Fate Of Meshmentioning
confidence: 99%
“…CH 3 S production from DMS H abstraction is the major pathway for SO 2 production from DMS, and the reactions of CH 3 S are therefore well studied (Barnes et al, 2006). Other studies have shown that the reaction of MeSH with OH occurs primarily at the S−H group (0.87 ± 0.03) forming CH 3 S, with a minor channel of H abstraction from the methyl group (0.13 ± 0.03) (Butkovskaya and Setser, 2021). Recent ab initio/RKKM calculations determined the CH 3 S yield from MeSH + OH at 298 K and 760 torr to be 0.98 (Mai et al, 2020).…”
Section: Atmospheric Fate Of Meshmentioning
confidence: 99%